EXAMINING EPIRA AND ITS EFFECT ON TECHNICAL AND OPERATIONAL EFFICIENCIES OF THE TOP FIVE PRIVATE DISTRIBUTION UTILITIES IN THE PHILIPPINES: SFA AND DEA APPROACHES - R. Acebedo, Kathrine Joyce; C. Bool, Nelson; R. Garcia, Dante (Humanities & Social Sciences Reviews, 2020)
Electric Industry. After two decades of EPIRAâ€™s enactment, it is essential to assess where in the Distribution Sector, the reformâ€™s trajectory has stalled. The study aimed to examine and assess the technical and operational efficiencies of the top five electric private distribution utilities (PDUs) in the Philippines under the regulatory policy. Methodology: This is a causal-comparative study using a panel data structure on technical and operational efficiencies of the top five PDUs in the Philippines from 1995 to 2014, employing quantitative measurement. This study used Data Envelopment Analysis (DEA) as the non-parametric test while Stochastic Frontier Analysis (SFA) as the parametric approach. Main Findings: Using the Stochastic Frontier Analysis (SFA) model showed that the implementation of EPIRA (post-EPIRA: 2001 to 2014) made the top five electric private distribution utilities in the Philippines more technically efficient in their operations than without the reform (pre-EPIRA: 1995 to 2000). It was also noted that PDUs with bigger franchise areas and older in existence were technically efficient in their operations than their smaller and younger PDUs counterpart, respectively. Applications: This study will enhance public awareness in the various assessment of regulatory policy arenas in PEI. Moreover, this study will also render useful insights into the management of DUs in the Philippines. Novelty/Originality of this study: An up-to-date empirical analysis of the situation to substantiate the claim of the reformâ€™s efficiency in the Philippines is lacking in the literature. This paper is thus providing a comprehensive theoretical debate by examining some indications of EPIRA’s efficiency in the Distribution Sector in the Philippines.